Fenomenologia techniki∗ - Ilnicki, Rafał (Wydawnictwo Naukowe UAM, 2011)
In this article I have shown what describes basic approaches to technics realized by phenomenologists. They are characterized by their strengths and weaknesses. Followed by this analysis I’m showing how this crisis of phenemonological method applied do technicization could be overcame by experimental phenomenology approach. I’m arguing that phenomenology of technics should be considered as an existential practice, not only as specialized process of conceiving instrumentalized phenomena. In the end I’m underlying consequences of that proposition.
Keywords: fenomenologia; phenomenology; technika; technics; eksperyment; experiment; zjawiska zinstrumentalizowane; instrumentalized phenomena